The impact of intangible capital on the territorial attractiveness of FDI in Morocco: econometric modeling - Zahra Mansouri (International Journal of Financial Studies, Economics and Management, 2022)
Since the speech from the throne of King Mohammed VI in 2014, on evaluating the intangible wealth of Morocco, intangible capital unanimous research. It is noted that wealth cannot be considered as capital that once identified, classified and evaluated. Before analyzing the correlation between intangible capital and attractiveness of the territory, it is first necessary to define, identify, mitigate and adapt this concept to the particularities and Moroccan background. Nobody can deny that Morocco is a country rich in its history, its culture, its heritage, its diversity and its people that wealth can be an engine of growth, value creation and even a source of attractiveness of territories. This is where our communication fits. Its purpose is to analyze the correlation between intangible capital and attractiveness of the Moroccan territory, for that Three points will be studied: Definition, identification and measurement of intangible capital; Study the context of the national debate on intangible capital; Analysis of the relationship between intellectual capital and attractiveness of the Moroccan territory.